Development of azimuthally not uniform processes in corona discharge in axially symmetric gap - Bolotov, O.V.; Golota, V.I.; Kadolin, B.B.; Karas΄, V.I.; Ostroushko, V.N.; Pashchenko, I.A.; Zavada, L.M. (Вопросы атомной науки и техники, 2013)
It is offered a hypothesis about connection between the experimentally observed sinuous trace of streamer with the instability of azimuthal harmonic of positive glow corona. The method of the instability analysis in linear approximation on two-dimensional mesh is described, and the calculations are carried out, which results show the instability existence. The calculations for higher harmonics corresponding to streamer bifurcation are carried out. Висунуто гіпотезу про зв’язок, що спостерігався в експерименті, звивистого сліду стримера з нестійкістю азимутальної гармоніки імпульсної позитивної корони. Викладено метод дослідження нестійкості у лінійному наближенні на двовимірній мережі та проведено розрахунки, результати яких свідчать про наявність нестійкості. Проведено розрахунки для вищих азимутальних гармонік, що відповідають галуженню стримера. Выдвинута гипотеза о связи наблюдаемого в эксперименте извилистого следа стримера с неустойчивостью азимутальной гармоники импульсной положительной короны. Изложен метод исследования неустойчивости в линейном приближении на двумерной сетке и проведены расчеты, результаты которых свидетельствуют о наличии неустойчивости. Проведены расчеты для высших азимутальных гармоник, соответствующих ветвлению стримера.